The power of purpose inspire teams, engage customers, transform business - O'Brien, John 1962 June 1-; Cave, Andrew (Pearson, 2017)
In a world where volatility is the new norm and change is a constant, the individuals and organisations that are flourishing are those with a clear sense of purpose based on authentic ethical values. Purpose is the secret ingredient - with purpose you have the key to exceptional performance, greater wellbeing and clarity in a VUCA world. But how do you find such purpose and ensure it propels your business forward? The Power of Purpose shares a simple 6-step framework you too can identify, clarify and shape your business purpose. You'll gain a competitive advantage and boost your bottom lin.
Includes index. - Includes bibliographical references and index. - Online resource; title from digital title page (viewed on August 30, 2017)
Keywords: Corporate culture; Organizational behavior; Leadership; Organizational effectiveness; Social responsibility of business; Culture organisationnelle; Comportement organisationnel; Efficacité organisationnelle; Entreprises; Responsabilité sociale; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior